Delineating and Calculating the Length of Yemen's Mainland Shoreline - Nagi, Hisham M. H. (International Journal of Alternative Fuels and Energy, 2021)
The Republic of Yemen is one of the countries gifted with a long coastal line. The coastal zone is rich with biodiversity and a wide range of coastal ecosystems, which is vital to the livelihood of the coastal communities. Despite the fact that several studies have described its coastal characteristics, there are still obvious variations in stating the actual length of its shoreline. In many reports and research studies, the coastline length of Yemen's mainland has been reported with different figures such as 1,906, 2,000, 2,100, 2,200 2,300, 2,350, and 2,520 km. This research paper aims to substantiate the actual shoreline length of Yemen, in addition, to calculate the length of each coastal governorate and district using GIS tools. This study showed that the total length of Yemen's mainland shoreline is about 2,252 km, with approximately 770 km overlooks the Red Sea and 1,482 km of the southern shoreline that overlooks the Gulf of Aden and the Arabian Sea. Among the coastal governorates of Yemen, Al-Hodeidah Governorate has been found to have the longest shoreline of about 519.7 km, whereas Hajjah Governorate has the shortest shoreline of about 92.7 km. As for coastal districts, Rudum District (Shabwah Governorate) has been found to have the longest shoreline of about 190.5 km. This research paper could provide some baseline information for other research works related to the coastal area of Yemen.